Phytochemical profile and toxicity of thyme-derived (Thymus vulgaris) essential oil against the exotic rugose spiraling whitefly (Aleurodicus rugioperculatus Martin) infesting coconut - Saneera, E.K.; Raguraman, S.; Suganthi, A.; Venkatesan, K. (Journal of Plantation Crops, 2022)
Microwave-assisted heat extraction of thyme (Thymus vulgaris) yielded 1.64 per cent w/v of yellow to amber coloured and less viscous oil with a peculiar aroma. GC-MS analysis revealed the presence of 20 compounds, out of which thymol (51.94%), p-cymene (14.5%), γ-terpinene (10.09%), linalool (3.48%), and endo-borneol (3.95%) were the major compounds. Eggs, second instar nymphs and pupae of rugose spiraling whitefly (RSW) were subjected to contact toxicity assessment by complete immersion (dip method) in various concentrations of thyme oil. The results showed that essential oils at 0.35 per cent concentration exhibited 100 per cent mortality in the second instar nymphs. Thyme oil (0.5%) inhibited egg hatching and adult emergence to the tune of 100 per cent when the eggs and pupal stages were treated. Probit analysis indicated that the median lethal concentration (LC50) of thyme oil to eggs, second instar nymph sand pupal stages were 0.19, 0.13 and 0.21 per cent, respectively. Thyme oil proved to be an excellent toxicant to different developmental life stages of RSW; hence it can be successfully incorporated into the integrated pest management (IPM) programme for whitefly management in the coconut ecosystem.